Electronic structure and magnetic properties of Co doped TiO2 thin films using X-ray absorption spectroscopy. (July 2015) - Kumar, Shalendra; Park, J.S.; Kim, D.J.; Lee, M.H.; Song, Tae Kwon; Gautam, Sanjeev; Chae, K.H.; Kim, S.S.; Kim, M.-H.
Abstract: The thin film of Ti0.95 Co0.05 O2− δ has been grown on LaAlO3 (100) substrate using pulsed laser deposition method. X-ray diffraction, near-edge X-ray absorption fine structure (NEXAFS) spectroscopy, X-ray magnetic circular dichroism (XMCD) and magnetic hysteresis loop measurements were used to fully understand the origin of ferromagnetism. Our structural analysis reveals a single phase nature of the film and excludes the presence of any secondary phase. NEXAFS spectra collected at Ti L 3, 2, and Co L 3, 2 -edge infer that Co and Ti ions are in 2+ and 4+ valence states, respectively. Multiplet calculation performed at Co L 3, 2 -edge also support the experimental observations and shows that Co ions are in 2+ valence state in O h (octahedral) symmetry. Zero field cooled and field cooled magnetization infer that T C of Ti0.95 Co0.05 O2− δ film is above room temperature. DC magnetization hysteresis loop study and XMCD measurement at Co L 3, 2 -edge reflect that Ti0.95 Co0.05 O2− δ film exhibits ferromagnetic ordering at room temperature.